The Effect of Sunscreen Use on The Incidence of Melasma in Police Officers: Meta-Analysis and Systemic Review - Putri, Intan Nurmawati; Putra, Aldo Primananda; Juniano, Nandika; Budi, Eko; Putri, Winawati Eka; Mayangsari, Renata; Prabawaningrum, Kinanti; Andriansyah, Julian (UNUSA Press, 2024)
Introduction: Melasma is a matter of concern for certain individuals due to its ability to cause changes in the visual appearance of the skin, ultimately impacting one's self-esteem and overall quality of life. Exposure to direct sunlight significantly influences the development of melasma. Indonesia's location below the equator results in a tropical environment with high temperatures throughout the year. Police officers are exposed to solar radiation for more than 6 hours every day while on duty. For certain police officers, particularly female officers, this is an issue as it can result in melasma, which affects appearances Objective: This study aims to estimate the effect of sunscreen usage in the police environment on melasma incidence in police officers. Methods: Electronic databases such as MEDLINE/PubMed, Cochrane Library, ClinicalTrials.gov, EBSCO, Scopus, ProQuest, Cambridge Core, reference lists, conference proceedings, and researchers in relevant fields of study were searched. The impact of sunscreen application on the prevalence of melasma in police personnel was evaluated using many parameters Results: Based on the systematic review, police officers continue to have a very high prevalence of melasma because they have a low awareness of the importance of using sunscreen. Conclusions: Awareness of sunscreen application on the skin is required to prevent the development of melasma in police personnel. Education on the prognosis, propensity, and chronicity of melasma is extremely important. In a police institution, Dermatovenereologists (DVE) play an important role.